Best Time to Begin Complementary Feeding of Full-Term Exclusively Breastfed Infants: Results of an Observational Study - Olga L. Lukoyanova; Tatyana E. Borovik; Vera A. Skvortsova; Leyla S. Namazova-Baranova; Natalya G. Zvonkova; Tatyana N. Stepanova; Elena A. Kopyltsova; Elena L. Semikina; Irina M. Guseva (Вопросы современной педиатрии)
Background: The article discusses a controversial issue of time for the introduction of complementary feeding for exclusively breastfed infants.Objective: Our aim was to determine the best time to begin complementary feeding of exclusively breastfed infants. Methods: Cohort observational study. We assessed actual nutrition and chemical composition of diets of infants, nalyzed anthropometric indicators, as well as clinical and biochemical parameters of blood.Results: The study included 203 infants. 112 of these infants were breastfed up to six months of age (exclusive breastfeeding or mixed feeding with the amount of breast milk of not less than 150–200 ml) and 91 infants were bottle-fed with adapted milk formulas. More than half of breastfed infants with complementary feeding introduction time of 4 and 5 months of age — 55 (57%) and only 4 (10%) exclusively breastfed infants received all necessary complementary foods by the age of 9 months. By the age of 9 months, diets of exclusively breastfed infants were 30–35% deficient in proteins, carbohydrates and energy, and 45% deficient in fat. Introduction of complementary feeding from the 4th month, rather than from the 5th or 6th month, reduces incidence of breast feeding in children aged 9 months up to 44% (p = 0.003). In the group of infants exclusively breastfed up to 6 months of age, the lowest concentration of ferritin in serum [median 28.0 (16.4; 45.0) ng/ml] was observed in this age. In this group, infants with unbalanced diets at the age of 9 months had the ferritin concentration of 11.7 (8.4; 22.6) ng/ml.Conclusion: The best time to begin complementary feeding of exclusively breastfed infants can be considered the age of 5 years.